Complement Clause C-Agreement Beyond Subject Phi-Agreement In Ikalanga - Letsholo, Rose; Safir, Ken (My University, 2019)
In this essay, we provide a rich description and analysis of C-agreement and complement clause complementizer (CCC) distributions in Ikalanga which reveals a highly articulated set of relationships between matrix clause properties and the morphology of an agreeing complementizer. In particular, we show that the agreeing CCC is sensitive not only to matrix subject phi-features, but to matrix voice and tense as well. Although the agreeing Cs are limited to a small set of predicates that are not fully predictable from meaning, the agreement facts are the same wherever an agreeing C is possible.
Keywords: Ikalanga; complement clause; C-agreement; NATURAL SCIENCES::Biology::Organism biology::Morphology